Pengaruh Tepung Biji Kecipir dan Tepung Pati Garut terhadap Kandungan Gizi dan Kalsium Bolu Kukus sebagai Inovasi Produk Sport Food: Effects of Winged Bean (Psophocarpus tetragonolobus L.) Seed Flour and Arrowroot (Maranta arundinacea L.) Starch on the Nutritional Composition and Calcium Content of a Steamed Sponge Cake as a Novel Sport Food - Hanin Salsabila Wardany; Nanang Nasrulloh (Amerta Nutrition, 2025)
Background: Adequate intake of protein and calcium is essential for muscle contraction and optimal athletic performance, yet hypocalcaemia and protein deficiency remain prevalent among Indonesian athletes. Innovation in locally based sports foods is therefore required. The combination of protein-rich winged bean (Psophocarpus tetragonolobus L.) seed flour and easily digestible arrowroot starch offers potential for developing a nutritious and acceptable steamed sponge cake. Objectives: To evaluate the effects of winged bean seed flour and arrowroot starch in steamed sponge cake formulations on nutrient composition, calcium content, and organoleptic properties as a sports food product. Methods: A completely randomized design was applied with three formulations: F1 (25%:75%), F2 (50%:50%), and F3 (75%:25%) ratios of winged bean seed flour to arrowroot starch, with two replications. Nutrient composition was analyzed using ANOVA followed by Duncan’s multiple range test, while organoleptic properties were assessed using the Kruskal–Wallis and Mann–Whitney tests. The best formulation was determined using the De Garmo method. Results: Ash content, total fat, energy from fat, total energy, carbohydrate, protein, and calcium differed significantly among formulations (p-value <0.001), whereas moisture content showed no significant difference (p-value >0.001). Organoleptic testing indicated no significant difference in color (p-value >0.001), while texture, aroma, and taste differed significantly (p-value <0.001). The optimal formulation was F3, containing 75%-winged bean seed flour and 25% arrowroot starch. Conclusions: Winged bean seed flour and arrowroot starch significantly influenced the nutritional and organoleptic characteristics of steamed sponge cake, highlighting its potential as an innovative local food–based sports food.